Switching Costs and Market Power in Auditing: Evidence from a Structural Approach - Guo, Qiang; Koch, Christopher; Zhu, Aiyong (The Accounting Review, 2024)
ABSTRACT This study provides novel evidence on the magnitude of switching costs in auditing. Using a discrete choice approach, we infer switching costs from clients’ audit firm choices. The demand estimation reveals that switching costs are significant and vary by direction, with the highest costs associated with switching from non-Big 4 to Big 4 audit firms. Counterfactual analyses of forced switches suggest that switching costs are substantial, ranging from 0.7 billion U.S. dollars (14.2 percent of audit fees) to 1.2 billion U.S. dollars (24.0 percent of audit fees) when aggregated across all clients. Counterfactual analyses of voluntary switching show that the audit market would become highly dynamic and more concentrated if switching costs were removed. Additionally, clients would gain consumer surplus of up to 306 million U.S. dollars (5.4 percent of audit fees) in such a scenario. Overall, our study documents the importance of switching costs for understanding audit market dynamics. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M42; M48; L11; L84.